Disperse Solid-Phase Extraction Cleanup for the Determination of 1-Deoxynojirimycin in Mulberry Leaves with Ultraperformance Liquid Chromatography-Tandem Mass Spectrometry - Lei Zhang; Yiran Zhou; Jing Meng; Jia Li (Journal of Food Quality)
A new determination method of 1-deoxynojirimycin (1-DNJ) in mulberry leaves based on ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) has been developed. Dried and crushed mulberry leaves’ sample was extracted by MeCN-water solvent, purified by graphitized carbon black (GCB) and primary secondary amine (PSA) to remove organic acids and pigments, and then analyzed after attenuation and filtration. The calibration curve showed linearity in the concentration range of 10–500 ng/mL, with the correlation coefficient of 0.998. Recoveries of spiked 1-DNJ at three fortification levels ranged from 94.6% to 96.4%, with relative standard derivation below 1.2%. Additionally, the matrix effect was assessed as negligible. Compared with methods by gas chromatography (GC) and liquid chromatography (LC) via real sample detection, the proposed method acquired better stability and detection efficiency. These results proved that this method has advantages of simple operation, complete purification, small pretreatment loss, good precision and accuracy, and high determination specificity, which is suitable for massive monitoring and precise quantitation of 1-DNJ in mulberry leaves.